Fabrication of electrochemical sensor for metronidazole using MoS2/graphite-like carbon nitride composite modified glassy carbon electrode - Ahmad, Khursheed; Raza, Waseem; Alsulmi, Ali; Kim, Haekyoung (Diamond and Related Materials, 2023)
Metronidazole (1-(2-hydroxyethyl)-2-methyl-5-nitroimidazole; MTZ) is widely used synthetic drug. MTZ has some negative effects on human being and aquatic life. Therefore, it is necessary to design and develop the MTZ sensor. Herein, hydrothermal method was used for the preparation of hybrid composite of molybdenum disulfide (MoS2) and graphitic carbon nitride (g-CN). The as-synthesized hybrid composite (MoS2/gCN) was further characterized by various techniques and methods which include powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). In further examinations, a glassy carbon electrode surface (3 mm diameter) was fabricated with the as-prepared MoS2/gCN composite. This fabricated MoS2/gCN/GCE (MGE-3) was further used as electrochemical sensor for the determination of MTZ. The investigations showed that an excellent detection limit of 0.099 μM can be achieved using MGE-3 as electrochemical sensor. A linear dynamic range of 2–125 μM was observed for the sensing of MTZ with relative standard deviation (RSD) value of 2.43 %.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Composite; Electrochemical sensor; Graphitic carbon nitride; Metronidazole; MoS